SULFONATED POLYIMIDES CONTAINING PYRIDINE GROUPS AS PROTON EXCHANGE MEMBRANE MATERIALS - Lei, Rui; Kang, Chuan-qing; Huang, Yun-jie; Qiu, Xue-peng; Ji, Xiang-ling; Xing, Wei; Gao, Lian-xun (Chinese journal of polymer science, 2011)
A series of sulfonated polyimides （SPIs） containing pyridine groups were prepared by direct polycondensation from 1,4,5,8-naphthalenetetracarboxylic dianhydride （NTDA）, 4,4＇-diaminodiphenyl ether-2,2＇-disulfonic acid （ODADS） and 4-（4-methoxy）phenyl-2,6-bis（4-aminophenyl）pyridine （DAM）. The resulting copolymers displayed good solubility in common organic solvents. Flexible, transparent, tough membranes were obtained via solution casting. All the films showed high thermal stability with desulfonation temperature over 300℃. They exhibited prominent mechanical properties with Young＇s modulus around 2.0 GPa. High proton conductivity （0.23 S/cm at 100% RH） was also observed. More importantly, the new materials exhibited low water uptake （30 wt%-75 wt% at 80℃） and improved water stability, which were attributed to the acid-base interaction between sulfonic acid and pyridine functional groups.